Factors Influencing Household Economic Welfare: A Systematic Literature Review - Prayitno, Putra Hilmi; Sahid, Sheerad; Hussin, Muhammad (Journal of Ecohumanism, 2024)
The article aims to systematically analyze the concept of household economic welfare and identify driving factors of household economic welfare. This study involved a systematic literature review to answer the research questions. The 18 most seminal were included and relevant to this study. The findings indicate that the theme of household economic welfare has been a major concern in various countries because of its impact on economic development. In addition, the findings show that income level, education, household access to credit, and social capital are the determinants of household economic welfare. This study provides implications to consider these determinants to promote household economic welfare and gives avenue for future scholars to elaborate on these variables.